The Conflict Management and Resolution through special powers under the Constitution of the Kingdom of Thailand B.E. 2557 (2014) (Interim), Section 44 after The coup of the National Council for Peace and Order (NCPO) - หน่อแก้ว, ยุทธศาสตร์ (CRRU Law, Political Science and Social Science Journal, 2021)
The constitutional powers in the history of Thai politics appeared in the country's highest law since B.E. 2502-2562 (1959-2019), totaling 6 times/issue, considered that it is the total power was given to the head of the coup and the prime minister to have the permission to order the special order without all of the verification in all cases. The section 44 has been successful in managing conflicts and controlling the political ideological groups in order, But the result found that there were the damage to the Thai people and Thai state in many cases as well. For example, the government's wrong decision about the international private, the order through a series of erroneous decisions made by the junta in a number of cases. The suggestion and advices about the special ability of the politic to people and group of people could divide in 3 points, The first one, the power to give the political ability to the specific people and group of people should not write in the constitution in all cases. The second one, the political management with the special power in crisis case should be under the context of the checking and balance power. The best way is to have the agency and the organization to check and verify the using of special power order as the same of the votes in the parliament followed by the principal of the balance power, in order to avoid the effect to people of Thailand and the long-term country management. Finally, the third one is about the reformation and control the army by the constitution provision to protect the coup d'etat, because the coup d'etat is the way to get the constitution provision of the political special power in all issue. So, the reformation of the army is the way to control the military under the civil government which is disabled the military to write the constitution that benefit to use the military power in the politic.